دليل نجاح المجتهدين في الستنباط - Shofiyullah Mukhlas (AHKAM : Jurnal Ilmu Syariah, 2014)
Success of Mujtahid in al-Istinbât. One cause of the emergence of the difference of opinion and legal fatwa toward events is the difference in the level of understanding of expert ulama in fiqh in comprehending phenomena altogether. Ijtihad is able to function at maximum if the conditions are fulfilled satisfactorily. The necessity for a systematic method and certain requirements in undertaking ijtihad does not mean limiting that ijtihad rather that legal product is not created from a instant process. The thinking of mujtahid whose systematic method is still a source of reference and inspiration to this day. Although there is a difference of opinion among them, all are easily analysed until the points are concluded. This paper also includes some verification methods of mujtahids and legal confusion which was has been instantly established.DOI: 10.15408/ajis.v14i1.1252